PERFORMANCE INVESTIGATION OF SPLIT-WALL AIR CONDITIONING: AN EXPERIMENTAL ANALYSIS OF COP AND EER WITH A CUSTOM DATA LOGGER - Anakottapary, Daud Simon; Artha Negara, I Gede; Ike Midiani, Luh Putu (Journal of Applied Engineering Science, 2026)
This investigation presents a comparative performance analysis of inverter and non-inverter air conditioning configurations under tropical climatic conditions, employing a custom-developed data logger system for real-time monitoring. The experimental investigation employed coefficient of performance (COP) and energy efficiency ratio (EER) as primary performance indicators. Both air conditioning configurations were evaluated at a standardized cooling capacity of 2.5 kW to ensure consistent comparative conditions. The experimental setup incorporated a custom-built data logger utilizing an ATmega 2560 microcontroller as the central processing unit, enabling real-time acquisition of thermal and electrical parameters critical for performance evaluation. Comprehensive sensor calibration procedures were conducted to ensure measurement reliability. The DS18B20 temperature sensors underwent rigorous calibration, yielding a mean absolute error (MAE) of ±0.75°C. This result demonstrates a high level of measurement accuracy and complies with established standard calibration acceptance criteria. Quantitative analysis revealed that the inverter system achieved a COP of 4.06, demonstrating 8.6% improvement over the non-inverter system’s COP of 3.74. Moreover, the energy efficiency ratio measurements showed the inverter system achieved an EER of 13.8, while the conventional system recorded 12.7, indicating 8.7% improvement. Additionally, the custom data logger demonstrated consistent reliability with multi-parameter measurement capabilities, enabling comprehensive monitoring of essential parameters for HVAC performance.